Peranan Staff Pastry Dalam Membuat Produk Sweet Bread Untuk Kepuasan Pelanggan Di Hotel Sahid Jaya - Triyono Arief Wahyudi; Martinus Hia (STREAMING, 2026)
This study examines the role of pastry staff in producing quality Sweet Bread and its influence on guest satisfaction at Hotel Grand Sahid Jaya. Using a descriptive qualitative design, data were gathered through six months of field practicum, participant observation, SOP and document review, interviews with pastry personnel and supervisors. The research positions Sweet Bread as a strategic hospitality product connecting technical craftsmanship, hygiene. Findings reveal four main quality drivers: careful raw-material and FIFO rotation, precise control of mixing through baking processes, adequate and well-maintained equipment, and strict food-safety practices. Operational constraints such as ingredient shortages, limited baking capacity, temperature variability, and labeling lapses were found to reduce consistency and increase waste. Human and managerial factors—including staff competence, teamwork, supervision, and creative presentation—significantly shape product reliability and guest perception. Strengthening SOP compliance, training, and quality audits enhances satisfaction and brand reputation